The construction of Malay identity in the media: a literature review / Siti Hajar Abd Aziz - Abd Aziz, Siti Hajar (2012)
What is the identity of the Malay and what Malay identity is being constructed by the media? This paper aimed at reviewing the construction of the Malay identity in the media from the literature as the foundation of a future research. The paper aimed at looking into history and past studies pertaining to the Malay identity in the media as a way to discuss the two questions asked. The study argues that the Malay identity constructed during the pre-colonial time by, is being constructed and reconstructed overtime by various elements and for various reasons. The researcher is particularly interested in explaining how the media, particularly the newspapers, construct and reconstruct the Malay identity. The review found out that the Malays identity were constructed by the British and were gradually constructed and reconstructed again by changes in political leadership and as well as to emphasis nation building among the Malaysian citizen. A more comprehensive studies is needed to look at the contemporary "Malay media identity‟ projected by the media and the factors influencing the identity.